A computational tool for the simulation and optimization of microbial strains accounting integrated metabolic/ regulatory information - Vilaça, Paulo (2011)
Background and scope Recently, a number of methods and tools have been proposed to allow the use of genome-scale metabolic models for the phenotype simulation and optimization of microbial strains, within the field of Metabolic Engineering (ME). One of the limitations of most of these algorithms and tools is the fact that only metabolic information is taken into account, disregarding knowledge on regulatory events. Implementation and performances This work proposes a novel software tool that implements methods for the simulation and optimization of microbial strains using integrated models, encompassing both metabolic and regulatory information. This tool is developed as a plug-in that runs over OptFlux, a computational platform that aims to be a reference tool for the ME community. Availability The plug-in is made available in the OptFlux web site (www.optflux.org) together with examples and documentation.